Efektivitas Fabula-Sjuzet Membentuk Defamiliarisasi dalam Kumpulan Cerpen Penulis Sumut Pasar Cerita Amaliun - Riyanto, Bambang (Jurnal Korpus, 2025)
Narrative structure plays a crucial role in the effectiveness of short stories, which must convey meaning within limited narrative space. This study aims to analyze the narrative structure of Pasar Cerita Amaliun, an anthology of short stories by North Sumatran writers, focusing on the relationship between fabula, sjuzet, and defamiliarization techniques. The research adopts a qualitative approach using descriptive-analytic methods. Data were collected through close reading of eleven selected short stories. The research instrument consisted of analytical categories assessing three aspects: clarity of fabula, complexity of sjuzet, and intensity of defamiliarization. Data analysis was conducted through narrative classification supported by simple quantitative tabulation. The findings reveal that most stories possess strong fabula, but only a few manage their sjuzet effectively. The short story “Celak Bu Haji untuk Dua Menantu” exemplifies the ideal synergy between fabula, sjuzet, and defamiliarization, producing a cohesive and aesthetically impactful reading experience. These results highlight the importance of narrative innovation and defamiliarization strategies to enhance the aesthetic quality of short fiction.